Narrative Analysis as a Means of Studying Individual Experience - Savchenko, Olena (East European Journal of Psycholinguistics, 2014)
The article presents the possibility of researching the individual experience on a personal level through the characteristics of the narrative forms` organization analysis. Traditional hermeneutical approach studies the narrative as a linguistic form that shows the personal experience of the subject, allows to structure, transform and be aware of it. The author emphasizes the basic properties of the narrative that represent features of the personal experience of the subject. The characteristics of autobiographical texts were identified that reflect such features of personal experience as consistency, openness and dialogicity. The author suggested the criteria that can be used in procedures of intent and content analysis to quantify the level of personal experience`s formation properties. References Almaev, N. (2012). Primeneniye Content-analiza v Issledovaniyakh Lichnosti: Metodologicheskiye Voprosy [Application of Content Analysis in Personality Research: Methodological Issues]. Moscow: Іnstitut psikhologii RAN. Chepeleva, N., Fedchenko, N. & Yakovenko, L. (2002). Tekst kak obiekt psikhologicheskogo issledovaniya [Text as an object of psychological research]. Aktualni Problemy Psykholohii, 2, 44–54. Kalmykova, Ye. & Mergentaler, E. (2002). Narrativ v psikhoterapii: rasskazy patsientov o lichnoi istorii (chast 1) [Narrative in psychotherapy: patients` stories about personal history (Part 1)]. Zhurnal Prakticheskoy Psikhologii i Psikhoanaliza, 1, 100–108. Lapshova, O. (2004). Psikhologicheskoye soderzhaniye teksta i yego otsenivaniye metodom intent-analiza i psikhosemantiki [Psychological content of the text and its evaluation by the method of intent analysis and psychosemantics]. Psikhologiya Vysshikh Kognitivnykh Protsessov, 236–249; Leontyev, D. (2004). Tematicheskii Appertseptivnyi Test [Thematic Apperception Test]. Moscow: Smysl. Problemy Psikhologicheskoy Germenevtiki [Problems of Psychological Hermeneutics] (2009). N. Chepeleva (Ed.). Kyiv: Mykhailo Drahomanov National Pedagogical University. Puzanova, Zh. & Trotsuk, I. (2003). Narrativnyi analiz: ponyatiye ili metafora? [Narrative analysis: concept or metaphor?]. Sotsiologiya: 4M, 17, 56–82.